Graphene-based 2D nanomaterials for solar cells - Safie, Nur Ezyanie; Azam, Mohd Asyadi (CRC Press, 2022)
Graphene, along with its derivatives, is pioneered among the family of two-dimensional nanomaterials, which compose an atomic crystalline single layer with outstanding and unique properties that make it a rising star material to be implemented in photovoltaic technology. Graphene has been acknowledged as an ideal option for integration with photovoltaic (PV) materials, and has played a multi-functional role in PV devices, including a transparent conductive electrode (TCE), charges transport medium, and interfacial layer. Graphene and its derivatives are also widely explored in the passivation and encapsulation method, especially in the emerging thin-film photovoltaic technology. Besides, graphene also plays a unique function in protecting photovoltaic devices from environmental deterioration because of its two dimensional honeycomb network structure, enabling long-term device protection to yield high efficiency and stability for PV devices. Flexible and thinner PV devices may function at the varied bending radius and exhibit no deterioration in device performance during bending testing thanks to graphene electrodes' excellent bending endurance. This outstanding achievement of graphene lays the path for a bright future of graphene-based flexible PV applications.